2013
DOI: 10.1155/2013/564547
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated within 28 Days In-Hospital Mortality of Patients with Acute Respiratory Distress Syndrome

Abstract: Objective. To determine the factors leading to in-hospital mortality within 28 days in hospitalized patients with ARDS. It was a prospective observational cohort study conducted in Intensive Care Unit of Aga Khan University Hospital Karachi from March to August 2011. Methodology. Data was collected from patients admitted in the intensive care unit on the basis of inclusion and exclusion criteria. The patients were followed daily for 28 days to record any in-hospital complications and the outcome of patients. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
4
10
0
4
Order By: Relevance
“…This result is similar with the study conducted by Sharif et al 8 which found that 90% of the survivors were below 65 years old. It has also been shown by the study from Zilberberg et al 9 that older age (>65 years) was independently associated with higher mortality rate among ARDS patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is similar with the study conducted by Sharif et al 8 which found that 90% of the survivors were below 65 years old. It has also been shown by the study from Zilberberg et al 9 that older age (>65 years) was independently associated with higher mortality rate among ARDS patients.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 77.3% of patients who survived have APACHE II score <20. This result is consistent with the other study conducted by Sharif N et al 8 There were several limitations in our study. The number of patients included was small due to the short duration of study.…”
supporting
confidence: 93%
“…21 In addition to the local effects, systemic inflammation is also muted, lessening the likelihood of MOF, a key cause of mortality in ARDS victims. 6,38 With the current project, we aim to identify if a narrow therapeutic window exists within which, if VPA is administered in our murine model of gram-negative pneumonia-induced ARDS, local and systemic inflammation as well as survival can be improved. We demonstrate that VPA administered systemically within up to 3 h from the primary inflammatory stimulus, both pulmonary and the systemic immune response can be muted to the extent that overall survival can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…5 The mortality of the syndrome is also very high, exceeding 45%—approaching 60% in the most severe cases 6 —making ARDS more lethal than embolic stroke and acute coronary syndromes. 7,8 Despite recent advances in critical care, treatment for ARDS remains largely supportive, 911 and targeted anti-inflammatory therapies have failed to improve clinically relevant outcomes in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ARDS patients were matched based on their Acute Physiology and Chronic Health Evaluation II (APACHE II) scores and age to determine the utility of ECMO in patients with a similar disease severity. The APACHE II assumes that mortality is affected by physiologic disturbances that occur early during the course of a disease [7]. In addition, we analyzed the discriminatory power and accuracy of the prognostic systems used on the day of ARDS diagnosis.…”
mentioning
confidence: 99%